Yield Performance Study of Bina Developed Sesame Varieties under Agro-Ecological Conditions of Mymensingh District in Bangladesh (Jagannath University Journal of Life and Earth Sciences, 2024)
An investigation was done during the Kharif-I (Summer) season 2022 at Sadar Upazilla of Mymensingh district in Bangladesh to explore the yield and factors affecting the yield of four sesame varieties developed by the Bangladesh Institute of Nuclear Agriculture (BINA). Three replications of a Randomized Complete Block Design (RCBD) were used, where Binatil-1, Binatil-2, Binatil-3, and Binatil-4 were the varieties. The experiment's findings showed that Binatil-1 contained the tallest plant (107.00 cm), whereas Binatil-3 contained the shortest plant (79.55 cm). It was noted that Binatil-2 had the greatest number of plant-1 branches (4.95), whereas Binatil-1 had the least amount (2.14). Additionally, Binatil-3 displayed the highest number of plant-1 pods (95.65), whereas Binatil-1 provided the lowest amount (51.27). Binatil-1 had the largest pod (3.56 cm), whereas Binatil-4 had the smallest (2.57 cm). It was noted that Binatil-1 displayed the greatest count of seeds in pod-1 (78.15), while Binatil-4 displayed the least amount (61.12). The highest 1000 seed weight was obtained from Binatil-2 (3.15 g), whereas the lowest 1000 seed weight was recorded in Binatil-1 (2.95 g). The established genotype Binatil-2 had the maximum seed yield (1.42 t ha-1), whereas Binatil-1 had the least (1.27 t ha-1). Among the cultivars, Binatil-3 matured in the fewest days (87), whereas Binatil-2 required the most days (95). At Binatil-2, significant yield performance was found from the Kharif-I (summer) season experiment. A simple correlation was done where branches per plant per thousand seed weight had a significant positive correlation and pod breadth had a negative impact on seed yield for all genotypes. This experiment will be helpful for oil crop breeders and the farming community to choose promising sesame genotypes with high yield potential and future breeding stock.Jagannath University Journal of Life and Earth Sciences, 9(2): 125–132, 2023 (December)